The Digital Public Sphere And The Face Of Indonesian Political Education - Muhammad Farid (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
The reporting of digital mass media vulgarly always sides with the interests. Is it siding directly, or is it in framing? Television shows and newspaper reports have become the public's 'breakfast'. The media increasingly determines the cognitive menu of people's everyday thoughts which are convincingly lulled that that is the most authentic. This article discusses the role of social media as a digital public space for Indonesian people's cognition. Using library research and critical and comparative analysis, this study aims to capture the primary ideas about media and political education in Indonesia within the theoretical framework of Jurgen Habermas' Public Sphere. This paper concludes that digital media plays a significant role in shaping the way of thinking of the public which tends to be co-opted to political power and capital owners. This way of thinking then forms a mass culture that is prone to authoritarianism. The findings of this research also serve as a warning to stakeholders who must be more vigilant in anticipating the globalization of digital media which can change the face of political education and the future of our democracy. Keywords: Social Media, Digital Public Space, Politics, Democracy